FIRST RECORDS OF THE SUBTERRANEAN TERMITES Procornitermes striatus (HAGEN) AND Procornitermes triacifer (SILVESTRI) (BLATTODEA, ISOPTERA, TERMITIDAE) IN MAIZE FIELDS IN ARGENTINA - Godoy, MarÃa Celina (REVISTA DE AGRICULTURA, 2019)
The genus Procornitermes is considered among the most important agricultural pest termites in South America. Here, the presence of P. striatus and P. triacifer on maize plants in Argentina is reported for the first time and the damages observed in the area are characterized. In May 2016, subterranean termites were detected in maize fields from Chaco province. They were identified as the aforementioned two species of the genus Procornitermes. The damages observed in the analyzed maize plants were concentrated in roots and at the stem base. The stems of affected plants were almost completely hollowed and many of the small diameter roots and rootlets had been cut and consumed or moved to the nests. These records reveal the presence of the subterranean Procornitermes termites in agricultural areas of Argentina and require future surveys to determine their abundance and potential impact on regional crops.